2016
DOI: 10.1007/s10802-016-0247-4
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Disorder-Specific Symptoms of Anxiety and Error-Monitoring Brain Activity in Young Children

Abstract: Anxiety disorders are among the earliest emerging disorders and most common mental health problem across the lifespan. A common characteristic of individuals with anxiety is poor attentional and cognitive control. Therefore, researchers are interested in how cognitive functioning relates to anxiety in young children. In particular, research has demonstrated associations between anxiety and electrophysiological markers of cognitive control skills such as the error-related negativity (ERN). The nature of the anx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 55 publications
0
18
1
Order By: Relevance
“… 1 It should be noted that the relationship between the ERN and anxiety symptoms may change across development ( Ip et al, 2019 ; Lo et al, 2017 ; Meyer, 2017 ; Meyer et al, 2012 , 2018). However, because the current study focuses on older children and adolescents, we do not fully review this literature in the current manuscript …”
mentioning
confidence: 99%
“… 1 It should be noted that the relationship between the ERN and anxiety symptoms may change across development ( Ip et al, 2019 ; Lo et al, 2017 ; Meyer, 2017 ; Meyer et al, 2012 , 2018). However, because the current study focuses on older children and adolescents, we do not fully review this literature in the current manuscript …”
mentioning
confidence: 99%
“…For example, Kujawa et al [] found a larger ERN in youth with SAD, but not in those with GAD, while the ERN relates to SAD and GAD in adults [Judah et al, ; Weinberg et al, ]. Interestingly, in young children (ages 5–8), a smaller ERN relates to greater separation anxiety symptoms [Lo et al, ], whereas in older youth (ages 10–17), a larger ERN relates to increased OCD symptoms [Carrasco et al, ], and more specifically, checking behaviors [Weinberg et al, ]. This developmental shift may be explained by a change from sensitivity to external (e.g., separating from the parent) to internal sources of threat [e.g., making a mistake in social situations, internal performance monitoring; Meyer, Hajcak, Glenn, & Klein, ; Weinberg et al, ].…”
Section: Additional Correlates Of the Ernmentioning
confidence: 99%
“…The prevalence of mental disorders in children and adolescents in the world reaches 13.4%, with the highest percentage of anxiety disorders of 6.5% compared to other mental disorders (Polanczyk, Salum, Sugaya, Caye, & Rohde, 2015). The onset of this disorder occurs on average between the ages of 6 and 17 years old (Auerbach et al, 2018;Lo et al, 2017;Merikangas et al, 2010;Polanczyk et al, 2015). Anxiety disorders in children can occur in various forms, such as separation anxiety, social phobia, generalized anxiety disorder, panic disorder with or without agoraphobia, obsessive-compulsive disorder, and specific phobias (Bulbena-Cabre et al, 2019;Canadian Mental Health Association, 2002;Rahmani & Moheb, 2010).…”
Section: Introductionmentioning
confidence: 99%